Characterization and Intraorganellar Distribution of Protein Kinases in Amyloplasts Isolated from Cultured Cells of Sycamore (Acer pseudoplatanus L.) - Alejandro M. Viale; Jarunya Ngernprasirtsiri; Takashi Akazawa (My University, 1991)
Incubation of amyloplasts isolated from cultured cells of sycamore (Acer pseudoplatanus L.) with [gamma-(32)P]ATP resulted in the rapid phosphorylation (half-time of 40 seconds at 25 degrees Celcius) of organellar polypeptides. The preferred substrate for amyloplast protein kinases was Mg(2+). ATP, and recovery of only [(32)P]serine after partial acid hydrolysis indicated the predominance of protein serine kinases in the organelle. These activities were located in the envelope and stromal fractions of the plastid, which showed different specificities toward exogenous protein substrates and distinct patterns of phosphorylation of endogenous polypeptides. A 66-kilodalton polypeptide, inaccessible to an exogenously added protease, was one of the major phosphorylated products found in intact amyloplasts at low [gamma-(32)P] adenosine triphosphate concentrations. This polypeptide represented the major phosphoprotein observed with the isolated envelope fraction. The patterns of polypeptide phosphorylation found in intact amyloplasts and chloroplasts from cultured cell lines of sycamore were clearly distinguishable. The overall results indicate the presence of protein phosphorylation systems unique to this reserve plastid present in nonphotosynthetic tissues.
Keywords: Acer pseudoplatanus; Amyloplast; Plant-Derived Bioactive Compounds